2007
DOI: 10.1111/j.1574-695x.2007.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased tolerance ofStaphylococcus aureusto vancomycin in viscous media

Abstract: The increased viscosity observed in biofilms, adherent communities of bacterial cells embedded in a polymeric matrix, was hypothesized to induce increased tolerance of bacteria to antibiotics. To test this concept, planktonic Staphylococcus aureus cells were grown and exposed to vancomycin in media brought to specific viscosities in order to mimic the biofilm extracellular polymeric matrix. A viscous environment was observed to decrease the vancomycin susceptibility of planktonic S. aureus to levels seen for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…In contrast, there were no significant differences in MRSA clearance by VAN within catheter biofilms formed by non-Rsp isolates. The precise mechanism(s) of this suboptimal MRSA clearance by VAN within non-Rsp-induced catheter biofilms is not well understood, but it will likely include their distinct biofilm compositions, limitations of VAN biofilm penetration, the evolution of "persister" cell populations within the depths of the biofilm, and/or VAN-induced enhancement of biofilm formation (13,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there were no significant differences in MRSA clearance by VAN within catheter biofilms formed by non-Rsp isolates. The precise mechanism(s) of this suboptimal MRSA clearance by VAN within non-Rsp-induced catheter biofilms is not well understood, but it will likely include their distinct biofilm compositions, limitations of VAN biofilm penetration, the evolution of "persister" cell populations within the depths of the biofilm, and/or VAN-induced enhancement of biofilm formation (13,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…4C). Furthermore, PEP35 was capable of reducing tissue bacterial burden when a potent biofilm-forming HA-MRSA strain (UC-18 [24,25]) was used (see Fig. S2 in the supplemental material).…”
Section: Pep35mentioning
confidence: 99%
“…First, they enrobe the bacteria in EPS, limiting the diffusion of biocides and antibacterials and their access to cells (Mah and O’Toole, 2001; Anderson and O’Toole, 2008). For example, a number of studies have shown a correlation between biofilm viscosity and antimicrobial sensitivity (Stewart, 1996; Gilbert et al ., 1998; Wirtanen et al ., 1998; Kostenko et al ., 2007; Ruhs et al ., 2013). Genetic disruption or chemical inhibition of biofilm formation also increases pathogen susceptibility to antimicrobial agents (Rashid et al ., 2000; Shih and Huang, 2002; Li and Lee, 2017).…”
Section: Introductionmentioning
confidence: 99%